Possible benefits of stretching for post-COVID-19 - N. Folha, Pablo; Bacurau, Reury; S. Aoki, Marcelo; Massa, Marcelo (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: COVID-19 is a new disease that causes severe health problems and is responsible for significant complications even after recovery, including disabilities that lead to motor impairment. In this sense, there is currently no protocol for physical exercises for people with physical disabilities caused by the disease. Therefore, it is necessary to find ways for individuals affected by this condition and experiencing motor difficulties to engage in physical activities, preventing their condition from deteriorating further after COVID-19. Objective: To present evidence that stretching improves strength, respiratory and vascular system function, enabling the return of individuals with physical deficits who are hindered from performing activities of daily living. Methods: This study is a literature review that analyzes the correlation between the benefits of active static stretching in individuals with physical disabilities post-COVID-19. The study collected data through accumulated scientific knowledge in the fields of clinical health and physical activity. The literature search was conducted using digital scientific databases, including SciELO, ScienceDirect, Bireme, and Google Scholar. Results: Muscle stretching is a physical activity that has shown promising benefits for post-COVID patients, however, further research in this field is needed. Conclusion: Through the presented studies, it can be concluded that stretching is a type of exercise that potentially can counterbalance various sequels caused by COVID-19, enabling the affected person to return to their daily routines.